JOMS: System architecture for telemetry and visualization on unmanned vehicle - Khalid, Hasnan; Saesar, Luhur Budi; M. S., Ikhmatiar; Herawan, Tutut (Elsevier Ltd, 2012)
This paper suggest a different way to get telemetry and visualization data from unmanned vehicle. A simple system architecture called JOMS (JOystick Modified System) is proposed to get those data. With the help of joystick, RC controller and simulink toolbox from MATLAB, the information from unmanned vehicle that associated with rotary and moving principle could be translated into useful data from the unmanned vehicle. Here, potentiometer from the joystick that acts as a variable resistor has been modified. The signals from joystick that interfaced on simulink are processed with some applied mathematical calibration regarding the functionality for certain condition of unmanned vehicle. To verify, the system module has been integrated both on unmanned ground vehicle (UGV) and unmanned air vehicle (UAV) for testing. Moreover, 3D virtual model was developed to ease the unmanned vehicle operator. Finally JOMS, the system architecture proposed successfully suggest a different way to get telemetry and visualization data from unmanned vehicle.